2017
DOI: 10.1177/1053451217736862
|View full text |Cite
|
Sign up to set email alerts
|

Developing a School-Based Multitiered Model for Self-Regulation

Abstract: Self-regulation is the control mechanism that enables a student to manage attention, emotion, behavior and cognition to engage in goal-directed actions, like learning. Too often, students atrisk for poor school outcomes do not enter school with strongly developed self-regulation skills and have difficulty developing them on their own. Self-regulation skills can be taught however, and are especially effective when introduced within the school setting. This manuscript describes a school based model for fostering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…өзін-өзі реттеуді бақылау механизмі деп атады, бұл білім алушыға мақсатты әрекеттерге қатысу үшін зейінді, эмоцияны, мінез-құлықты және қабылдауды басқаруға мүмкіндік береді. Сонымен қатар, Парк және т. б. өзінөзі реттеу -бұл танымдық, мінез-құлық және эмоционалды дағдылар, адамдарға қажетті мақсаттарға жету үшін тиімді жұмыс істеуге мүмкіндік береді, әсіресе стресс жағдайында деп анықтады [12].…”
Section: негізгі бөлімunclassified
“…өзін-өзі реттеуді бақылау механизмі деп атады, бұл білім алушыға мақсатты әрекеттерге қатысу үшін зейінді, эмоцияны, мінез-құлықты және қабылдауды басқаруға мүмкіндік береді. Сонымен қатар, Парк және т. б. өзінөзі реттеу -бұл танымдық, мінез-құлық және эмоционалды дағдылар, адамдарға қажетті мақсаттарға жету үшін тиімді жұмыс істеуге мүмкіндік береді, әсіресе стресс жағдайында деп анықтады [12].…”
Section: негізгі бөлімunclassified
“…Odinokaya et al (2019) also defined it as the students' ability to critique and evaluate external behavior and mental activity; whereas, according to Al-Rab'a and Mukablah (2019, p. 435), self-regulation is the ability of the individual to understand their learning, to develop knowledge and trends, to control emotional behaviors, to focus and actively participate in a group, and to monitor progress towards achieving goals. Webb et al (2018) referred to self-regulation as the control mechanism that enables the student to manage attention, emotion, behavior, and perception to participate in goal-oriented actions. Besides, Park et al (2019) indicated that selfregulation is the cognitive, behavioral and emotional skills that allow individuals to work efficiently towards achieving their desired goals, especially when they are under stress Listiana et al (2020) argued that self-regulation includes the skills of time management, planning and managing strategies, and perseverance in completing difficult tasks.…”
Section: Self-regulationmentioning
confidence: 99%